(untitled) (Research, Society and Development, 2020)
The impact generated from the land use modifications reflects expressively in the components of the hydrological cycle, affecting the use of the natural resources. This work aims to evaluate the soil occupation dynamics in the Caiabi, Nandico and Celeste river basins located in the northern region of the State of Mato Grosso between 1986 and 2015. Geoprocessing techniques such as false color combinations and supervised classification were applied using the maximum likelihood estimation (maxver). Two thematic classes of land occupation were defined, forest and anthropized. The results are presented in thematic maps showing the spatial distribution of changes in soil cover. It was concluded that 44% of the forest area was removed between 1986 and 2015. The greatest change in the soil cover occurred between 1997 and 2006, resulting in a reduction of 1017.0 km2 of forest area.